Assessment of the Potential for Greenhouse Gas Emission Mitigation by the Methanization of Slaughterhouse Waste in the District of Abidjan (Côte d’Ivoire) - Kone, Tiangoua; Clarisse Mangoua-Allali, Amenan Lydie; Ama-Cauphys, Assamoi Béatrice; Hadidjata Kone, Pantchie; Jean-Marie Ouattara, Pétémanagnan; Coulibaly, Lacina (European Scientific Journal, ESJ, 2022)
Abattoirs are a source of huge waste that contributes to global greenhouse gas (GHG) emissions and, thus, to global warming and climate change. This study aimed to evaluate the GHG emission mitigation potential of a biodigester to be installed at the abattoir of Port-Bouët in the District of Abidjan. Mathematical methods developed by Hashimoto, Gwogon, and Amahrouch and an empirical method were used to assess this mitigation potential. The results showed that regardless of the methods, biogas volumes increased from 2013 to 2017 and decreased in 2018. The highest daily biogas production was obtained in 2017 for all the methods. According to Hashimoto’s method, the biogas volume was 564.50 m3 in a biodigester of 2792.64 m3. Gwogon’s method led to a biogas volume of 724.15 m3 for a 2228.14 m3 biodigester. The calculated volume of biogas with the Amahrouch method was 557.03 m3 for a 2785.17 m3 biodigester. The empirical method showed a maximum biogas volume of 631.31 m3. The amount of CO2 avoided per kilogram of dung ranged from 41579.88 to 71561.17 kg CO2e, 41643.46 to 71670.58 kg CO2e, 41689.19 to 71749.30 kg CO2e for Gwogon, empirical and Hashimoto methods, respectively. The values ranged from 41694.30 to 71758.10 kg CO2e for the Amahrouch method. These results show a biodigester’s tremendous environmental and economic potential for treating the waste of the slaughterhouse of Port-Bouët.